2021
DOI: 10.3390/jcm10071487
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Unit Improves Pregnancy Outcomes in Women with Rheumatic Diseases and Hereditary Thrombophilias: An Observational Study

Abstract: Rheumatic diseases (RD) and hereditary thrombophilias (HT) can be associated with high-risk pregnancies. This study describes obstetric outcomes after receiving medical care at a multidisciplinary consultation (MC) and compares adverse neonatal outcomes (ANOs) before and after medical care at an MC. This study is a retrospective observational study among pregnant women with RD and HT treated at an MC of a university hospital (southern Spain) from 2012 to 2018. Absolute risk reduction (ARR) and number needed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In total, 1154 people were enrolled in studies comparing intervention and a control group (5 RCTs and 5 cohort studies); 498 patients (mean age: 36.18, SD ± 6.64 years) were included in intervention arms and 656 patients (mean age: 38.40 SD ± 6.77 years) in comparator arms. Two studies did not report the mean age of participants [ 13 , 16 ]. Median disease duration in intervention and comparator groups amounted to 9.5 years (IQR: 7.23–11.35) and 9 years (IQR: 7–10.25), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 1154 people were enrolled in studies comparing intervention and a control group (5 RCTs and 5 cohort studies); 498 patients (mean age: 36.18, SD ± 6.64 years) were included in intervention arms and 656 patients (mean age: 38.40 SD ± 6.77 years) in comparator arms. Two studies did not report the mean age of participants [ 13 , 16 ]. Median disease duration in intervention and comparator groups amounted to 9.5 years (IQR: 7.23–11.35) and 9 years (IQR: 7–10.25), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of adverse neonatal outcomes in standard care was 42.8% in SLE and 90% in APS. However, after the introduction of the MD team, the risk of adverse neonatal outcomes reduced to 36.7% (95% CI: 21.3–52.1) in the SLE group and 87.5% (95% CI: 77–98) in the APS group [ 13 ]. Similar results were observed by Wind et al, who found that maternal outcomes in SLE and primary/secondary APS patients were 36/71 in the historically treated cohort versus 22/41 in the MD-treated one (OR 0.91, 95% CI 0.38–2.17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Referral to excellence clinics means increased monitoring and being well taken care of before, during and after pregnancy, especially when a multidisciplinary approach is organised, as it is well known that working across medical fields ensures best care for patients. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Referral to excellence clinics means increased monitoring and being well taken care of before, during and after pregnancy, especially when a multidisciplinary approach is organised, as it is well known that working across medical fields ensures best care for patients. 23 In addition, it is evident that the organisation of training and educational activities both for HCPs as well as for patients and families is crucial in providing a tangible contribution to improve the experience of patients and also to better support the patient-clinician relationship.…”
Section: Discussionmentioning
confidence: 99%